2011
DOI: 10.1088/0004-637x/729/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Model Atmospheres and the Cooling of the Solar System's Giant Planets

Abstract: We compute grids of radiative-convective model atmospheres for Jupiter, Saturn, Uranus, and Neptune over a range of intrinsic fluxes and surface gravities. The atmosphere grids serve as an upper boundary condition for models of the thermal evolution of the planets. Unlike previous work, we customize these grids for the specific properties of each planet, including the appropriate chemical abundances and incident fluxes as a function of solar system age. Using these grids, we compute new models of the thermal e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
164
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(187 citation statements)
references
References 94 publications
(227 reference statements)
18
164
4
1
Order By: Relevance
“…As demonstrated by Guillot et al (2004), the inclusion of alkali metals enhances the opacity enough to ensure convection at all depths within a present-day Jupiter. Our models, which include modern opacities and self-consistently allow for radiative transport wherever ∇ rad < ∇ ad , confirm this result: the intermediate radiative window is only mildly subadiabatic (∇ − ∇ ad ∼ −10 −1 ) and vanishes before t ∼ 2 × 10 8 yr (see also Fortney et al 2011), and has an insignificant effect on the overall cooling time. Thus for the homogeneous phases of the evolution, our models may be directly compared to models constructed assuming ∇ = ∇ ad always.…”
Section: Modes Of Heat Transportsupporting
confidence: 74%
See 1 more Smart Citation
“…As demonstrated by Guillot et al (2004), the inclusion of alkali metals enhances the opacity enough to ensure convection at all depths within a present-day Jupiter. Our models, which include modern opacities and self-consistently allow for radiative transport wherever ∇ rad < ∇ ad , confirm this result: the intermediate radiative window is only mildly subadiabatic (∇ − ∇ ad ∼ −10 −1 ) and vanishes before t ∼ 2 × 10 8 yr (see also Fortney et al 2011), and has an insignificant effect on the overall cooling time. Thus for the homogeneous phases of the evolution, our models may be directly compared to models constructed assuming ∇ = ∇ ad always.…”
Section: Modes Of Heat Transportsupporting
confidence: 74%
“…We apply the self-consistent model atmospheres of Fortney et al (2011) as fit analytically by Leconte & Chabrier (2013), which provide the temperature at the 10 bar level T 10 as a function of surface gravity g and intrinsic temperature T int . The planet's effective temperature T eff in a given timestep is given by…”
Section: Model Atmospheresmentioning
confidence: 99%
“…Conventional models based on fully adiabatic thermal profiles notably lead to cooling times about 15% longer than the age of the solar system for Jupiter (Fortney et al 2011). In principle, the hotter non-adiabatic internal structures suggested in the present paper will prolong the cooling and thus worsen the problem.…”
Section: Initial Heavy Element Distributionmentioning
confidence: 78%
“…Despite their similar masses, radii, and compositions, thermal evolution models of Uranus and Neptune suggest that right after their formation, Neptune may have been relatively luminous but Uranus relatively faint (e.g. Hubbard & Macfarlane 1980;Fortney et al 2011). Stevenson (1986) suggested that this dichotomy may be accounted for if a violent head-on collision yielded a hot and homogeneous interior of Neptune, whereas an oblique collision caused a tilted Uranus with a stably-stratified interior.…”
Section: Discussionmentioning
confidence: 99%